Keterwakilan Perempuan Dalam Pemilihan Umum Legislatif Tahun 2019 Di Kota Jambi Provinsi Jambi Melalui Perspektif Gender - Pratama, Rizki; Nurdin , Nurliah; Meltarini , Meltarini (UIR Press, 2025)
This research aims to determine the phenomenon of gender stereotypes that often occurs, especially in work. Gender stereotypes are general views or prejudices regarding the attributes or characteristics, or roles that women and men should have or carry out. Gender stereotypes regarding women's roles then limit their abilities and even career choices, including in politics. This stereotype is closely related to the position where women and men have their respective places in social life. In the political context, the role and position of women is quite clearly discriminated against. This stereotype has been built up in the minds of society for a long time, which has led to low levels of women's electability even though it has been accommodated through affirmative regulations. This research uses qualitative research methods. Researchers apply in-depth interview techniques, where researchers will interview informants or subjects in depth. The interactive model analysis technique is reducing, presenting data and concluding data which is carried out interactively with a cyclical data collection process. Conclusions are drawn by observing the narrative text resulting from the data presentation. Drawing conclusions aims to describe the answer to the research problem formulation. The results of the research show that the representation of women as legislative candidates will ultimately return to how the democratic system shapes perceptions of women's position in politics as seen from the data. Data on elected legislative candidates in 2019 in Jambi City shows that there are only eight female legislative members out of a total of 45 legislative candidates. selected. Cadre formation is an important part of the role and function of political parties. It is not surprising that two (2) of the total eight (8) female legislative candidates elected are party cadres contesting with serial number 1. The priority of cadre numbering is important in this case considering that people's assumptions about numbers are still very strong. This also applies to other legislative candidates from competing parties. If we examine further, the majority of elected candidates with the largest number of voters and vote contributions from parties are legislative candidates with serial numbers from small to large. The reasons for the low electability of women in the 2019 legislative elections in Jambi City based on the indicators above include the still dominant stigma of men in Indonesian society as breadwinners and obliged to work. Politics, which in this case is considered work, makes it an open struggle between men and women regardless of their motivation. This is called a patriarchal culture which places men in the work domain.